#TITLE_ALTERNATIVE# - WILLIAM SUTANTO (NIM 13303008), RIARDY
High school students spend many of their study activities in the classroom, which many of them feel the room is thermally uncomfortable. The current observation and study was carried out to investigate and quantify the level of thermal comfort in a particular classroom. The observation was carried out repeatedly during a span of time to look for variation of responses there may be shown by the occupying students. The responses were studied out of the distributed questionnaires during the observations, along with the simultaneously measured thermal variables in the particular classroom. The measured variables were the dry-bulb, and globe temperatures, the airflow velocity and the air relative humidity. The thermal comfort level in the particular classroom endured by the students, along with their thermal condition preferences were observed. The thermal comfort responses were compared to the thermal comfort standard known as PMV (Predicted Mean Vote). Moreover, all of the subjectsÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’ responses from each question in questionnaires were gathered and analyzed thoroughly in this research paper. Gender difference was taken into account in this study as well.